Live imaging of Arabidopsis development - Wangenheim, Daniel von; Daum, Gabor; Lohmann, Jan U.; Maizel, Alexis (Arabidopsis Protocols, 2014)
Live cell imaging is an essential methodology for studying the structure, dynamics, and functions of cells in a living plant under normal or stressed growth conditions. Arabidopsis thaliana is perfectly amenable to various live microscopy techniques. In this chapter, we provide guidelines to design live-imaging experiments. We discuss specifically the respective advantage of each microscopy technique, the choice of reporter, and the preparation of the sample. Detailed protocols for imaging of shoot and roots are provided.